The Return of Expansionary Austerity : Firms' Investment Response to Fiscal Adjustments in Emerging Markets - Magud, Nicolas (IMF Working Papers; Working Paper, 2022)
We study the response of corporate investment in Emerging Markets to unexpected fiscal shocks. We find that, although firm-level investment decreases on impact following unexpected public expenditure adjustments (classical Keynesian multiplier effect), it quickly rises above pre-shock levels. The rebound in investment is facilitated by fiscal space, flexible exchange rates, and more predictable fiscal policy. We also show that the composition of fiscal adjustments matters for investment's response-compared to public investment adjustments, reductions in public consumption lead to larger private investment contractions on impact, but drive private investment to above pre-shock levels. Finally, we exploit firm-level heterogeneity in several dimensions, including to show that corporate investment's recovery is stronger in firms in the tradable sector and in larger and less indebted firms, and to show that the long-run benefits to economic activity of the fiscal shock appear to outweigh its short-run costs.